Factor Effecting the Selecting Behavior Towards the Artificial Turf Football Field in Case Study of Winning Seven’s Customer - Bumrungpanictaworn, Apittai (Journal for Developing the Social and Community, 2019)
The objective of this research was to study the factor affecting the behavior of selecting the artificial turf football field in case of the winning seven football field's service user by using the quantitative research with 245 people, and brought the data for analyzing the descriptive statistics, such as the frequency, the average and the standard deviation. The result found that the marketing mix affecting the behavior of selecting the artificial turf football field of WINNING SEVEN artificial turf football field in overall was high. The product comment was high, and the second was the marketing, the price, the physical description, the distributed channel, the process and the personnel respectively. In the aspect of the product shall focus on the quality of the surface and the standard size of the artificial turf football field. In the aspect of the price focus on the proper service price with the field's quality. The place for the distribution channels shall focus on the convenience in traveling of the service user. In the aspect of the marketing shall focus on the hours accumulation for discounting the next service, and having the discount for the member/loyalty members. In the aspect of the personnel shall focus on the hospitality to the service user. In the aspect of the process shall focus on the quickness of the service. In the aspect of the physical description shall focus on the cleanness and the beauty of the field, and the behavior in using the football field service which is most of them play football for exercising 1-2 times per week on Monday to Friday from 6.00 p.m. to 8.00 p.m. They play about 2 hours. The most influence to the making decisions for using the service was friend.